Study of Microclimate of Pepper (Piper nigrum L.) in various Agroforestry Systems - Sanjaya, Refki; Pangestika, Padhina (Hasanuddin University, 2024)
One of Indonesia's centres of pepper plant yields is Lampung Province. The productivity of the pepper is decreasing. Pepper productivity is declining, so selecting the right crop system, according to the needs of the microclimate of pepper plants, is needed to produce optimal productivity. This research aims to study the microclimate variations of several agroforestry systems, analyze the relationship of microclimate productivity, determine the ideal type, and evaluate the level of pepper productivity in various systems. This research was conducted in Aji Kagungan Village, Abung Kunang District, North Lampung Regency, at 450-1500 meters above sea level in January-April 2019. The research method used was survey purposive sampling, which considered the uniformity of the age of pepper plants and differences in the types of vegetation that make up the system. The data observed were microclimate, land condition, and productivity of pepper plants. Data was collected on five types of systems divided into four zones. Each zone has four observation points, observations were made 8 times with an interval of 10 days. The results showed that the determinants of microclimate diversity of pepper agroforestry systems were canopy area, density, frequency, and vegetation. In contrast, the magnitude of sunlight transmission, temperature, and humidity in pepper agroforestry systems was influenced by vegetation characteristics. The form of relationship formed by the transmission of sunlight and air temperature is positive linear, while the humidity of the air forms a negative linear relationship to the productivity of pepper plants in the agroforestry system tested while of the five types of agroforestry systems tested. Type 5 is the ideal pepper agroforestry system. Where the microclimatic conditions formed by Type 5 can produce the highest pepper productivity among other system types